The contribution of participation on individual success in sports: examining the impact of sports participation on performance outcomes - Raisalam Angoy; Amung Ma'mun; Agus Mahendra; Bambang Abduljabar; Rhea Mae Lim; Jessel Gay Wacan; Procopio Galendez Jr; Genifer Ramoso (Journal of Physical Education (Maringá), 2025)
Sports participation has long been recognized as a key contributor to athletic success, which is influenced by both physical fitness and performance outcomes.  However, though, this is true, there are other factors in sports participation, which are very crucial for sports success among them are: years of active sport participation, years of training experience, training volume, and competition level, among others. This means that understanding the relationship between factors is critical for optimizing sports involvement and athlete development, particularly in competitive settings where small improvements can lead to significant advantages. Basing on this, the present study examines the impact of sports participation on the performance outcomes of college basketball players across the four campuses of Mindanao State University in the Philippines. Forty-eight males’ university athletes were surveyed regarding their sports involvement, looking at their years of active sport participation, years of training experience, training volume and competition level, and their game performance was analyzed following notational statistics data. The study employed a quantitative descriptive design, analyzing the data using Spearman rho to assess the strength of the relationships. The findings revealed that players with over 7 years of active participation performed better (r = 0.780, p = 0.000), also, there is a strong positive correlation between training experience and performance (r = 0.768, p = 0.000). Training volume was also found to positively influenced performance (r = 0.640, p = 0.000), while higher competition levels were moderately associated with improved performance (r = 0.538, p = 0.000). These results suggest that long-term sports involvement, consistent trainings and exposure to high-level competition are essential for achieving better athletic performance outcomes. In conclusion, the study highlights the importance of sustained sports participation, regular training, and competitive exposure, especially in universities, to enhance athletic performance of the participants. Upon this, it is recommended that coaches, trainers, physical educators and sports program developers should encourage long-term training and frequent participation in higher-level competitions. However, for better results, future researches should investigate the role of psychological and technical factors in sports performance.Keywords: Philippine basketball, training program, performance, participation